(untitled) (Research, Society and Development, 2020)
Objective: To know the social representations of women in relation to the choice of delivery mode. Methodology: Descriptive, exploratory study with a qualitative approach, based on the theoretical framework of social representations. The research was carried out in a usual risk maternity hospital, through an interview with 20 mothers. The collected data were transcribed in full and organized manually. To discuss the results, the Theory of Social Representations according to Moscovici was used. Results: After the content analysis according to Bardin, three thematic categories emerged: information for choosing the mode of delivery, idealization of delivery, and women’s autonomy in choosing the mode of delivery. Conclusion: it was noticed that the perception and effectiveness of female autonomy in the obstetric scenario still does not represent a predominant reality in public health services when it comes to choosing the mode of delivery. However, it is respect for the autonomy of women during pregnancy, childbirth and birth that makes them feel socially represented as the protagonist in this process.